Handbook of jealousy : theory, research, and multidisciplinary approaches - Hart, Sybil, 1954-; Legerstee, Maria Theresia, 1944-; Wiley InterScience (Online service) (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2010)
Through a compilation of original articles, the Handbook of Jealousy offers an integrated portrait of the emerging areas of research into the nature of jealousy and a forum for discussing the implications of the findings for theories of emotional and socio-cognitive development.: Presents the most recent findings and theories on jealousy across a range of contexts and age-stages of development; Includes 23 original articles with empirical findings and detailed commentaries by leading experts in the field; Serves as a valuable resource for professionals in the fields of clinical psychology, psy.
Background. Jealousy in Western History / Peter N Stearns -- Loss, Protest, and Emotional Development / Michael Lewis -- Jealousy and Romantic Love / Aaron Ben-Ze'ev -- Socio-Biological Foundations. The Ontogenesis of Jealousy in the First Year of Life / Sybil L Hart -- Neural Structures of Jealousy / Gabriela Markova, James Stieben, Maria Legerstee -- The Evolutionary Sources of Jealousy / Jaak Panksepp -- Sibling Rivalry in the Birds and Bees / Scott Forbes -- Green Eyes in Bio-Cultural Frames / Vasudevi Reddy -- Cognitive Underpinnings. Social Bonds, Triadic Relationships, and Goals / Maria Legerstee, Baila Ellenbogen, Tom Nienhuis, Heidi Marsh -- Jealousy in Infant Peer Trios / Ben S Bradley -- Parental Reports of Jealousy in Early Infancy / Riccardo Draghi-Lorenz -- Jealousy in Autism Spectrum Disorders (ASD) / Nirit Bauminger -- Is Jealousy a Complex Emotion? / R Peter Hobson -- What Is Missing in the Study of the Development of Jealousy? / Joseph J Campos, Eric A Walle, Audun Dahl -- Social-Emotional Foundations within the Parent-Child-Sibling Context. A Theoretical Model of the Development of Jealousy / Sybil L Hart -- Jealousy and Attachment / R M Pasco Fearon, Marian J Bakermans-Kranenburg, Marinus H van Ijzendoorn -- The Development of Sibling Jealousy / Brenda L Volling, Denise E Kennedy, Lisa M H Jackey -- The Socialization of Sibling Rivalry / Sybil L Hart -- Socio-Emotional Foundations within Other Eliciting Contexts. Family Triangular Interactions in Infancy / Elisabeth Fivaz-Depeursinge, Nicolas Favez, Chlǒ Lavanchy Scaiola, Francesco Lopes -- Culture, Parenting, and the Development of Jealousy / Heidi Keller, Bettina Lamm -- Social Class, Competition, and Parental Jealousy in Children's Sports / Noel Dyck -- When Friends Have Other Friends / Jeffrey G Parker, Sara A Kruse, Julie Wargo Aikins -- Jealousy in Adulthood / Christine R Harris, Ryan S Darby -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Jealousy; PSYCHOLOGY -- Emotions; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement; Jealousy; Jaloezie; Electronic books; Handboeken (vorm)